2019
DOI: 10.1001/jamanetworkopen.2019.7242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Trial Changes in Primary Outcome and Reported Intervention Effect Size Between Trial Registration and Publication

Abstract: Key Points Question Does primary outcome change between trial registration and publication alter a randomized clinical trial’s reported intervention effect size? Findings In this cross-sectional study that included 389 trials, 130 of them had at least 1 primary outcome change between registration and publication. This significantly overestimated the reported intervention effect size by 16% compared with those without primary outcome change. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…If investigators choose the method of analysis based on trial data in order to obtain more favourable results (often referred to as 'p-hacking'), this can cause bias [7,8]. Selective reporting has been identified previously, where outcomes with more favourable results are more likely to be reported than other outcomes [9][10][11][12][13][14][15][16][17][18][19][20]. There is some evidence to suggest this may also be a concern for statistical analyses; pre-specification of proposed methods in protocols is often poor, discrepancies between protocols and publications are common, and in some instances, changes may have been made to obtain specific results [5,9,11,14,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…If investigators choose the method of analysis based on trial data in order to obtain more favourable results (often referred to as 'p-hacking'), this can cause bias [7,8]. Selective reporting has been identified previously, where outcomes with more favourable results are more likely to be reported than other outcomes [9][10][11][12][13][14][15][16][17][18][19][20]. There is some evidence to suggest this may also be a concern for statistical analyses; pre-specification of proposed methods in protocols is often poor, discrepancies between protocols and publications are common, and in some instances, changes may have been made to obtain specific results [5,9,11,14,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This composite outcome, which was not listed among primary or secondary outcomes in the trial’s protocol (ClinicalTrials.gov NCT03400800), included cardiac death, non-fatal myocardial infarction, and stroke as well as an imprecisely defined component described as “any signs or symptoms of cardiac arrest.” Information allowing appraisal of the validity of these results is also unavailable. In general, reported outcomes not listed in trial protocols have larger effect sizes than outcomes identified in advance 8. Although reductions in LDL cholesterol were listed as the primary and secondary outcomes in the trial protocol, these are surrogate endpoints—not all cholesterol lowering drugs have lived up to initial expectations of disease prevention and lower mortality 89…”
Section: Inaccessible Resultsmentioning
confidence: 99%
“…In general, reported outcomes not listed in trial protocols have larger effect sizes than outcomes identified in advance 8. Although reductions in LDL cholesterol were listed as the primary and secondary outcomes in the trial protocol, these are surrogate endpoints—not all cholesterol lowering drugs have lived up to initial expectations of disease prevention and lower mortality 89…”
Section: Inaccessible Resultsmentioning
confidence: 99%
“…Because of this, an outcome may be considered only fully specified when all 5 elements are present (10). Given the five possible elements that constitute an outcome and a difference in criteria required by international standards (3 elements), it can be considered an adequately reported outcome one that is partially defined (with a domain, measure and time point) or even fully specified (if all 5 possible elements are present) being defined in the registry in a retrospective manner (6,8,9,(11)(12)(13)(14)(15)(16). In this example, "mean change from baseline of Beck Depression Inventory score 12-month post randomization", stated in the primary outcome section in a registry (done prospectively -before the initiation of the clinical trial) in clinicaltrials.gov platform (or other platform) with a registry number (13), would be considered a fully specified outcome (10) and hence adequately reported (13).…”
Section: Introductionmentioning
confidence: 99%